Level of choreographic preparedness of sportsmen of different age groups in sports aerobics - Valentina Todorova (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the analysis of choreographic preparedness of different age groups of sportsmen on sports aerobics. Material & Methods: videos of competitive programs of the sportsmen, who are specialized in aerobics, different age groups, method of expert evaluations are used for the quantitative analysis of choreographic preparedness; methods of mathematical analysis and synthesis are used for the determination of level of choreographic preparedness of sportsmen. Results: the level of choreographic preparedness is determined on the basis of the rating scale of the criteria of implementation of the competitive programs (Competition rules of 2013-2016) of teams-participants of the Championship of Ukraine for sports aerobics. Conclusions: indicators, to which it is necessary to pay attention in the course of choreographic preparation at stages of long-term training of sportsmen, are defined.